Performance of low-frequency structures incorporated with rate-independent linear damping. (15th February 2019) - Luo, H.; Ikago, K.; Chong, C.; Keivan, A.; Phillips, B.M.
Highlights: Rate-independent linear damping benefits a low-frequency structure. A control algorithm that mimics rate-independent linear damping is proposed. A passive implementation of approximated rate-independent linear damping presented. Analytical examples exemplify the feasibility of the proposed model. Abstract: This study examines the performance of rate-independent linear damping incorporated into a low-frequency structure subjected to strong ground motion. Linear viscous damping and rate-independent linear damping are known to yield similar response displacements and velocities during earthquakes. If the central response frequency is close to the fundamental frequency of the structure, the two linear damping elements yield almost identical damping forces. However, if the two frequencies differ significantly, these two damping elements yield substantially different damping forces, resulting in substantially different floor-response accelerations. The benefit of rate-independent linear damping in a low-frequency structure is that it yields relatively low floor-response accelerations, even when the structure is subjected to ground motion containing high-frequency components. In contrast, linear viscous damped structures can suffer high accelerations induced by high damping forces caused by high-frequency components in ground motion. Thus, rate-independent linear damping is expected to be more effective in controlling floor-response accelerations without increasing the response displacements. To simulate the behavior of rate-independent linear damping for practical applications, both active and passive methods are proposed. We found that a passive model containing a Maxwell element and a negative stiffness element in parallel is a viable option for mimicking the behavior of rate-independent linear damping and thereby improving the seismic performance of low-frequency structures subjected to strong ground motion.